2015
DOI: 10.1016/j.expneurol.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A novel and robust conditioning lesion induced by ethidium bromide

Abstract: Molecular and cellular mechanisms underlying the peripheral conditioning lesion remain unsolved. We show here that injection of a chemical demyelinating agent, ethidium bromide, into the sciatic nerve induces a similar set of regeneration-associated genes and promotes a 2.7-fold greater extent of sensory axon regeneration in the spinal cord than sciatic nerve crush. We found that more severe peripheral demyelination correlates with more severe functional and electrophysiological deficits, but more robust centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…A CL is a purposeful peripheral nerve insult prior to definitive injury and repair, with the aim of enhancing axon regeneration. Parameters that appear to affect the CL response include the (1) method of conditioning, (2) location of the CL, (3) magnitude of the insult, (4) duration of conditioning effect, (5) CL interval, and (6) type of nerves suitable for conditioning . A summary of the findings is shown in Table .…”
Section: What Is a Cl?mentioning
confidence: 99%
See 1 more Smart Citation
“…A CL is a purposeful peripheral nerve insult prior to definitive injury and repair, with the aim of enhancing axon regeneration. Parameters that appear to affect the CL response include the (1) method of conditioning, (2) location of the CL, (3) magnitude of the insult, (4) duration of conditioning effect, (5) CL interval, and (6) type of nerves suitable for conditioning . A summary of the findings is shown in Table .…”
Section: What Is a Cl?mentioning
confidence: 99%
“…Heightened inflammation induced by macrophages improves axon regeneration, and when macrophages are eliminated in the milieu, axon regeneration is significantly reduced. Hollis et al echoed the importance of macrophages by simulating a CL using ethidium bromide injected into the sciatic nerve . The increased number of macrophages in the DRGs was associated with a robust growth of the peripheral axons.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The tape removal test showed deficits after C4 lesion (Bradbury et al, ) but only minor deficits in another study (Fagoe et al, ), and no effect on the similar adhesive dot removal task was found after C1 lesion (Ballermann et al, ). Significant deficits were found on the narrow beam (Bradbury et al, ; Hollis et al, ) and rotarod (Hollis et al, ), with cervical lesions. Skilled reaching tasks have also been assessed in cervical lesions.…”
Section: Assessment Of Regeneration and Functional Recoverymentioning
confidence: 99%
“…Several other studies employ sensory tests that are primarily developed for nociceptive function and were used to investigate perceptual abnormalities in treatment groups or neuropathic pain states as a result of the lesion (Chan et al, ; Andrews et al, ; Hollis et al, ). For this aim, thermal and mechanical hyperalgesia can be assessed with Hargreaves and Von Frey tests.…”
Section: Assessment Of Regeneration and Functional Recoverymentioning
confidence: 99%
“…Interestingly, recent work from the Zou lab demonstrated a novel ethidium bromide-induced conditioning lesion (Hollis et al, 2015). Here, when injected into the sciatic nerve, ethidium bromide acted as a demyelinating agent and induced prototypical regeneration associated genes as well as robust central regeneration that surpassed that induced by traditional nerve crush.…”
Section: Re-activation Of Intrinsic Growthmentioning
confidence: 99%